Two-step ESD: an option for en-bloc resection of extensive colorectal laterally spreading tumors - Kawaguti, Fabio S.; Okazaki, Ossamu; Miyajima, Nelson T.; Segateli, Vanderlei; Marques, Carlos F.S.; Nahas, Caio S.R.; Martins, Bruno C.; Nahas, Sergio C.; Junior, Ulysses R.; Filho, Fauze M. (Endoscopy International Open, 2019)
Background and study aims Endoscopic submucosal dissection (ESD) is considered feasible and safe for treatment of colorectal laterally spreading tumors (LST), However it remains a challenge in case of extensive lesions even for experts. This study aimed to describe a new method to facilitate ESD of extensive colorectal LSTs. Between July 2010 and January 2018, 140 patients underwent ESD for colorectal LSTs. Four of them were submitted to two-step ESD and were included in this retrospective study. The submucosal dissection of lesions larger than 12 cm started and continued until the medical team decided to pause the procedure and continue it in a second step. The second procedure was performed 2 days after to finish the en-bloc resection.Three patients were male, with mean age of 67.2y (± 2.2). All lesions were located in the rectum, with a mean size of 153.7 mm (± 33.8). En-bloc and curative resection were successfully achieved in all cases. Mean duration of the first step of the procedure was 255 minutes (± 61.8), and mean duration of the second step was 205 minutes (± 205). Overall mean duration of both steps was 460 minutes (± 168). Mean dissected area in the first step of the procedure was approximately 55 % of the lesion. No adverse events were observed. In conclusion, our results suggest that performing ESD in two steps could be a feasible and safe option for exceptional cases in which is not possible to finish the procedure in one step, avoiding the morbidity of surgical treatment.